2016
DOI: 10.1017/s1049023x15005543
|View full text |Cite
|
Sign up to set email alerts
|

Mass-gathering Events: The Role of Advanced Nurse Practitioners in Reducing Referrals to Local Health Care Agencies

Abstract: Appropriately trained and experienced ANPs working within event medical teams have a positive impact on referral rates from mass-gathering events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…According to our results, multi-authority collaboration in the pre-event planning phase manifests, for example, as consultation of an EMS specialist regarding the planned attendee numbers, and the competence of the on-site medical care provided in the emergency plan. Previous studies showed that having medical professionals available among the first-aid providers and the use of treat-and-release directives have an impact on the need for transport to hospital, and in turn affect the workload for the EMS system and healthcare facilities [15,16,18,21,23]. According to an Australian study by Zeitz et al [8], the increase in workload for the rescue service in mass gatherings with a total of 5.7 million attendees in a two-year period, was only minor.…”
Section: Co-operation In the Pre-planning Phasementioning
confidence: 99%
See 2 more Smart Citations
“…According to our results, multi-authority collaboration in the pre-event planning phase manifests, for example, as consultation of an EMS specialist regarding the planned attendee numbers, and the competence of the on-site medical care provided in the emergency plan. Previous studies showed that having medical professionals available among the first-aid providers and the use of treat-and-release directives have an impact on the need for transport to hospital, and in turn affect the workload for the EMS system and healthcare facilities [15,16,18,21,23]. According to an Australian study by Zeitz et al [8], the increase in workload for the rescue service in mass gatherings with a total of 5.7 million attendees in a two-year period, was only minor.…”
Section: Co-operation In the Pre-planning Phasementioning
confidence: 99%
“…Sufficient first-aid capability and the quality of security emerged from the results along with other needed services, such as taking care of water supply. Previous studies indicated that on-site medical staff should include health professionals along with first-aid providers [15,18,19,23,40]. According to Locoh-Donou et al [26], absence of free drinking water is strongly associated with patient presentations.…”
Section: Factors To Be Noted In the Emergency Planmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the risks due to lack of support on resources and inefficiency of gatherings’ safety recognized in this domain were reported as Lack or shortage of patient care workers such as Physicians or Paramedics;[181926313336] flow directions;[20] risk assessment;[20] communication;[20] pre-event advice;[23] a plan for vaccination before gatherings;[2526] coordination;[26] free water as well as terrorist attacks; difficult access to water and food;[28] difficult access to medical facilities;[262732] and duration of MG.[38]…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, environmental risks threatening the health of participants in MGs included weather risks such as cold, environmental heat,[1215161718192021222324252627282930313233343536373839404142] precipitation,[12] higher humidity,[121520313842] long distance of gatherings and austere environment,[18] mobility of population,[3142] gatherings in outside (external) and unbounded venues,[32] MGs exposed to traffic accidents,[19] the participants’ number and crowd density,[15182028293139] insect bites, and sunburns. [40]…”
Section: Discussionmentioning
confidence: 99%